Integrating Environmentally Sustainable Construction In The Architectural Design Education At Universiti Teknologi MARA, Malaysia - Amat, Sufian Che (2010)

(untitled)
The design studio teaching methods is recognised as the foundation of most design curricula as traditionally practiced by Ecole de Beaux Arts and Bauhaus. However it is increasingly being scrutinised as to its effectiveness in shaping future professionals relative to the quality of the built environments. This study proposes an instrument that can be used to numerically assess level of integration of environmentally sustainable construction education in design studios. A survey is conducted using random strata sampling technique among undergraduate students.